Portraits of Edo and Early Modern Japan : The Shogun's Capital in Zuihitsu Writings, 1657-1855 /: The Shogun's Capital in Zuihitsu Writings, 1657-1855. ([2019]) - Groemer, Gerald, 1957-
No abstract available